Medical Students and Patients Benefit from Virtual Non-Medical Interactions Due to COVID-19. (July 2021) - Coe, Taylor M; McBroom, Trevor J; Brownlee, Sarah A; Regan, Karen; Bartels, Stephen; Saillant, Noelle; Yeh, Heidi; Petrusa, Emil; Dageforde, Leigh Anne
Background: Patient care restrictions created by the COVID-19 pandemic constrained medical students' ability to interact directly with patients. Additionally, organ transplant recipients faced increasing isolation due to the rise of telemedicine, the importance of social distancing and their immunosuppressed state. We created a pilot program to pair students with transplant patients for structured, virtual encounters and studied its impact on medical students and patients. Methods: In May 2020, medical students conducted virtual visits with patients via telephone or video conferencing. Patients and students were surveyed regarding their experiences and independent focus groups were conducted. The survey responses and focus group discussions were deidentified, transcribed, and analyzed for themes. Results: Ten participating students were in their first, second, or final year of medical school. The 14 patients were liver or kidney transplant recipients or kidney donors. All interactions lasted longer than 30 minutes, with 56% greater than 1 hour. Three themes emerged related to the student experience: improvement of their clinical communication skills, development of knowledge and attitudes related to organ transplantation and donation, and independent management of a patient encounter. Three themes related to the patient experience: appreciation of the opportunity to share their personal patient experience to help educate future physicians, a cathartic and personally illuminating experience and an opportunity to share the message of donation. Conclusions: This pilot program provided a novel opportunity for virtual student-patient interactions that was feasible, well-received, and mutually beneficial. The use of virtual non-medical patient experiences allowed for experiential learning during which students learned about both clinical medicine and enhanced their communication skills directly from patients. Additionally, patients were able to engage with medical students in a new way, as teachers of clinical interactions, and reported a high level of satisfaction in addition to deriving personal benefit.